Smart health : International Conference, ICSH 2014, Beijing, China, July 10-11, 2014. Proceedings - Zeng, Daniel; Chen, Hsinchun; Zhang, Yong; Xing, Chunxiao; Neill, Daniel B.; Zheng, Xiaolong (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the International Conference for Smart Health, ICSH 2014, held in Beijing, China, in July 2014. The 21 papers presented together with 4 extended abstracts were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on information sharing, integrating and extraction; health data analysis and management; clinical and medical data mining; and clinical practice and medical monitoring.